Physicochemical Parameters of Surface Seawater in Malaysia Exclusive Economic Zones Off the Coast of Sarawak - Farah, Akmal Idrus; Chong, Melissa Dennis; Nur Syazwani, Abd Rahim; Masania, Mohd Basri; Jamil, Musel (Universiti Malaysia Sarawak, (UNIMAS), 2017)
Physicochemical characteristics of seawater play crucial role for productive marine ecosystem and fisheries activities. The limited information of Sarawak surface seawaters provide objective to determine the physicochemical characteristics in Malaysia Exclusive Economic Zone off the Coast of Sarawak. A total of 38 samples were collected using Van Dorn Waals Sampler and the physicochemical characteristics were measured using physicochemical parameter probes. Ranges for dissolved oxygen (DO) was 3.73-6.83 mg/l, temperature was 27.03-30.13ºC, pH was 7.63-7.82, salinity was 33.77-36.77 ppt, turbidity was 0.01-1.01 NTU, chlorophylla concentration was 0.01-4.52 mg/l, nitrate was 0.01–0.08 mg/l, nitrite was 0.001–0.012 mg/l and phosphate was 0.01–5.95 mg/l. There was positive correlation between chlorophyll-a and nutrients that indicated the biological uptake by biota (e.g. phytoplankton). In conclusion, the present study shows that the Malaysia Exclusive Economic Zone off the Coast of Sarawak had minimal pollution based on Malaysia Marine Water Quality Criteria. An update for physicochemical characteristics of surface seawaters in the coverage areas is required as future work.